A computational study of effects of material properties, strain level, and friction coefficient on smart stent behavior and peripheral artery performance during the interaction process. (March 2022) - Nematzadeh, Fardin
Peripheral artery stenting (PAS) is an effective alternative for peripheral endarterectomy. Smart stents can be used to minimize the problems of interaction between peripheral arteries and smart stent. To evaluate the biomechanical properties of smart stents and their interactions with the peripheral artery, a 3D nonlinear finite element method (FEM) model that was composed of a peripheral artery and a smart stent was built. The present simulation modeled smart superelasticity material based on thermodynamics of the Helmholtz free energy (Auricchio theory) and Peripheral artery based on hyperelastic models (Mooney-Rivlin and Ogden). Additionally, the present study used FEM to assess the influences of the material properties, strain level, and friction coefficient (with attention to smart stent's materials properties) of the newly designed smart stent during crimping and its interaction with the peripheral artery. The results showed that the smart stent with high Af : Austenite finish temperature, 90% crimping, and friction coefficient of 0.1 between smart stent and peripheral artery performed better mechanically and clinically, which can be attributed to suitable Chronic Outward Force (COF), high Radial Resistive Force (RRF), whole mechanical hysteresis regarding superelastic performance, the high martensite formation, the low stress on the peripheral artery, and the high strain on the internal curvature of the smart stent and peripheral artery. Moreover, it was found that the Mooney-Rivlin model showed a better mechanical performance that the Ogden model given the distribution of stress and strain level on the peripheral artery. These models were appropriate for the description of the peripheral artery performance and smart stent behavior with considering material properties, strain level, and friction coefficient during the interaction process.